Understanding the relationships among dispositional mindfulness, PsyCap, creative motivation, and creative performance: a sequential mediation model - He, Wu-jing; Zhang, Kai (Frontiers in Psychology, 2025)
Drawing on insights from positive psychology theory and conservation of resources (COR) theory, the present study explored how dispositional mindfulness affects creativity through the sequential mediating effect of two positive psychological constructs—psychological capital (PsyCap) and creativity motivation. A total of 658 undergraduates in Hong Kong (51.3% female; Mage = 20.9 years) completed the study. Dispositional mindfulness, PsyCap, and creativity motivation were measured via the Chinese versions of the Mindful Attention Awareness Scale, the revised Compound PsyCap Scale, and the Creativity Motivation Scale, respectively. Regarding creativity, a multidimensional assessment approach was used to evaluate creative performance across three dimensions—idea production, creative combination, and restructuring problem solving—by using three creativity tests: (1) a divergent thinking test, (2) a gestalt combination test, and (3) a creative problem-solving test. Mediation analyses revealed that PsyCap and creativity motivation partially but significantly mediated the effect of dispositional mindfulness on all three dimensions of creativity as sequential mediators, while the residual direct effect suggested the possibility of additional unexamined pathways. These findings shed light on the psychological mechanism of positive human functioning in relation to positive personal attributes, psychological resources, and creative functioning.